2018
DOI: 10.1371/journal.ppat.1006994
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection in immunocompetent pregnant mice causes fetal damage and placental pathology in the absence of fetal infection

Abstract: Zika virus (ZIKV) infection during human pregnancy may cause diverse and serious congenital defects in the developing fetus. Previous efforts to generate animal models of human ZIKV infection and clinical symptoms often involved manipulating mice to impair their Type I interferon (IFN) signaling, thereby allowing enhanced infection and vertical transmission of virus to the embryo. Here, we show that even pregnant mice competent to generate Type I IFN responses that can limit ZIKV infection nonetheless develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
109
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 48 publications
9
109
0
1
Order By: Relevance
“…Ferrets often have large litters, strengthening their attractiveness as an animal model to study viral infections. It is not clear why select animals in a litter become more strongly infected than others and show different characteristics, but similar outcomes have been reported for human pregnancies in that only a fraction of women with Zika virus infections give birth to infants with microcephaly; in addition, maternal infection levels and fetal outcome may not be strongly related (Brasil, et al, ) (Szaba et al, ). A recent report by the CDC, however, suggests that babies born to infected mothers show symptoms consistent with learning disabilities as they develop over the first year or two of life.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Ferrets often have large litters, strengthening their attractiveness as an animal model to study viral infections. It is not clear why select animals in a litter become more strongly infected than others and show different characteristics, but similar outcomes have been reported for human pregnancies in that only a fraction of women with Zika virus infections give birth to infants with microcephaly; in addition, maternal infection levels and fetal outcome may not be strongly related (Brasil, et al, ) (Szaba et al, ). A recent report by the CDC, however, suggests that babies born to infected mothers show symptoms consistent with learning disabilities as they develop over the first year or two of life.…”
Section: Discussionmentioning
confidence: 87%
“…This may also partially explain why we did not see a viral titer in the blood of the mother, if the placenta is an important site of Zika replication. Szaba et al ()) reported that even low levels of maternal infection can cause substantial placental infection and variable effects in the fetus. In addition, each placenta may not have the same access to the virus through its individual umbilical vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, placental vascular development was dysregulated by in utero ZIKV infection, as evidenced by a significant decrease in endothelial cell density. This disruption to the normal placental architecture may have affected the anchoring of the placenta into the uterine wall and the nutrient exchange between the dam and fetuses, which are necessary for fetal development (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…The Model relevance was also discussed in the context of a Zika pregnancy model in immunocompetent mice, in which the infected dams did not get viremia and there was no detectable vertical transmission of virus, yet there was virtually 100% fetal demise. Monoclonal antibody blocking studies indicated that, despite the absence of productive infection, the pathology was apparently caused by virus, raising the possibility of fetal demise due to specific placental pathology [7]. There would be great value in developing high quality, standardized animal models and challenge strains of particular pathogens that are broadly accepted.…”
Section: Sessionmentioning
confidence: 99%